Metformin Stimulates FGF21 Expression in Primary Hepatocytes. (15th October 2012) - Nygaard, Eva B.; Vienberg, Sara G.; Ørskov, Cathrine; Hansen, Harald S.; Andersen, Birgitte
Abstract : Fibroblast growth factor 21 (FGF21) is a novel metabolic regulator of glucose and lipid metabolism; however, the exact mechanism of action and regulation of FGF21 is not fully understood. Metabolic status plays an important role in the regulation of FGF21, and we therefore examined whether metformin, an indirect AMPK-activator, regulates FGF21 expression in hepatocytes. FGF21 mRNA and protein expression were determined after incubation of primary cultured rat and human hepatocytes with metformin for 24 hours. To study the role of AMPK in the putative regulation of FGF21, hepatocytes were incubated with Compound C (an AMPK inhibitor) in the presence of metformin. A strong dose-dependent increase in FGF21 expression was observed in both rat and human hepatocytes treated with metformin. This effect was blocked by addition of the AMPK-inhibitor Compound C. The study shows that metformin is a potent inducer of hepatic FGF21 expression and that the effect of metformin seems to be mediated through AMPK activation. As FGF21 therapy normalizes blood glucose in animal models of type 2 diabetes, the induction of hepatic FGF21 by metformin might play an important role in metformin's antidiabetic effect.